we have given integral is:
\[
I = \int_{\pi/11}^{9\pi/22} \frac{dx}{1 + \sqrt{\tan x}}.
\]
To simplifying the integral, rewrite it as:
\[
I = \int_{\pi/11}^{9\pi/22} \frac{\sqrt{\cos x} \, dx}{\sqrt{\sin x} + \sqrt{\cos x}}.
\]
Next, perform a substitution: Let
\[
x \to \frac{\pi}{2} - x.
\]
Under this substitution, the following transformations occur:
\[
\sin x \to \cos x, \quad \cos x \to \sin x, \quad dx \to -dx.
\]
This changes the integral to:
\[
I = \int_{\pi/11}^{9\pi/22} \frac{\sqrt{\sin x} \, dx}{\sqrt{\cos x} + \sqrt{\sin x}}.
\]
Let this new integral be denoted as \( I_2 \). Now, by adding the original integral \( I \) and the substituted integral \( I_2 \), we get:
\[
I + I_2 = \int_{\pi/11}^{9\pi/22} \frac{\sqrt{\cos x} + \sqrt{\sin x}}{\sqrt{\cos x} + \sqrt{\sin x}} \, dx.
\]
Simplifying the right-hand side:
\[
I + I_2 = \int_{\pi/11}^{9\pi/22} 1 \, dx.
\]
The limits of integration give:
\[
\int_{\pi/11}^{9\pi/22} 1 \, dx = \left[ x \right]_{\pi/11}^{9\pi/22} = \frac{9\pi}{22} - \frac{\pi}{11}.
\]
Simplifying this result:
\[
\frac{9\pi}{22} - \frac{\pi}{11} = \frac{9\pi}{22} - \frac{2\pi}{22} = \frac{7\pi}{22}.
\]
Thus, \( I + I_2 = \frac{7\pi}{22} \). Since \( I = I_2 \), we have:
\[
2I = \frac{7\pi}{22}.
\]
Solving for \( I \):
\[
I = \frac{7\pi}{44}.
\]
Final Answer:
\[
\boxed{\frac{7\pi}{44}}
\]